Statin use is associated with a lower risk of recurrence after curative resection in BCLC stage 0-A hepatocellular carcinoma - Shih-Yu Yang; Chih-Chi Wang; Kuang-Den Chen; Yueh-Wei Liu; Chih-Che Lin; Ching-Hui Chuang; Yu-Chieh Tsai; Chih-Chien Yao; Yi-Hao Yen; Chang-Chun Hsiao; Tsung-Hui Hu; Ming-Chao Tsai (BMC Cancer, 2021)
Abstract Background Use of statins is associated with a reduced risk of hepatocellular carcinoma (HCC). However, the effect of statin use on HCC recurrence is unclear. This study aimed to evaluate the effect of statin use on recurrence after curative resection among patients with HCC. Methods We retrospectively assessed 820 patients with Barcelona Clinic Liver Cancer (BCLC) stage 0 or A HCC who underwent primary resection between January 2001 and June 2016 at Kaohsiung Chang Gung Memorial Hospital. Exposure to statins was defined as use of a statin for at least 3 months before HCC recurrence. Factors that influenced overall survival (OS) and recurrence-free survival (RFS) were analyzed using Cox proportional hazards models. Results Of the 820 patients, 46 (5.6%) used statins (statin group) and 774 (94.4%) did not (non-statin group). During the mean follow-up of 76.5 months, 440 (53.7%) patients experienced recurrence and 146 (17.8%) patients died. The cumulative incidence of HCC recurrence was significantly lower in the statin group than the non-statin group (p = 0.001); OS was not significantly different between groups. In multivariate analysis, age (hazard ratio [HR]: 1.291; p = 0.010), liver cirrhosis (HR: 1.743; p < 0.001), diabetes (HR:1.418; p = 0.001), number of tumors (HR: 1.750; p < 0.001), tumor size (HR: 1.406; p = 0.004) and vascular invasion (HR: 1.659; p < 0.001) were independent risk factors for HCC recurrence, whereas statin use (HR: 0.354; p < 0.001) and antiviral therapy (HR: 0.613; p < 0.001) significantly reduced the risk of HCC recurrence. The statin group still had lower RFS than the non-statin group after one-to-four propensity score matching. Conclusion Statins may exert a chemo-preventive effect on HCC recurrence after curative resection.